The Influence of Education Level and Work Experience on Employee Performance at Taman Nongsa Indah Village Batam - Agnesti Novela; Pasaribu (Journal of Multidimensional Management, 2025)
This study examines whether education level and work experience shape employee performance at Taman Nongsa Indah Village, Batam. Using a quantitative, associative cross-sectional design, all 60 permanent employees were surveyed (total sampling). Education level (13 indicators) and work experience (12 indicators) were measured via structured questionnaires; performance used company evaluation data. After meeting classical assumptions, multiple linear regression showed: education level had no significant effect on performance (t = 1.077, p = 0.286); work experience had a negative, significant effect (t = −2.948, p = 0.005; β = −0.432); jointly, both predictors were significant (F = 4.537, p = 0.015) with R² = 0.137. Descriptively, performance averaged 81.63—below the company target of 85. The counter-intuitive negative effect of experience is discussed through burnout, complacency, technology-adaptation gaps, appraisal bias, and career-plateau issues. Managerial implications include anti-burnout initiatives, revitalized training (including digital upskilling), appraisal redesign to capture mentoring/complex problem-solving, clearer career paths, and performance-linked rewards. Future research should incorporate additional determinants (e.g., motivation, leadership, culture) and longitudinal designs to probe non-linear experience–performance dynamics.